Rembrandt and his circle : insights and discoveries - Dickey, Stephanie (Amsterdam studies in the Dutch golden age., 2017)
This collection brings together art historians, museum professionals, conservators, and conservation scientists whose work involves Rembrandt van Rijn and associated artists such as Gerrit Dou, Jan Lievens, and Ferdinand Bol. The range of subjects considered is wide: from the presentation of convincing evidence that Rembrandt and his contemporary Frans Hals rubbed elbows in the Amsterdam workshop of Hendrick Uylenburgh to critical reassessments of the role of printmaking in Rembrandt's studio, his competition with Lievens as a landscape painter, his reputation as a collector, and much more. Developed from a series of international conferences devoted to charting new directions in Rembrandt research, these essays illuminate the current state of Rembrandt studies and suggest avenues for future inquiry. "Skilfully chosen and edited by Stephanie Dickey, these papers were presented at the highly successful conferences on Rembrandt and his pupils held at Herstmonceaux Castle in recent years. This is cutting-edge Rembrandt scholarship full of valuable insights and new discoveries." -- Christopher Brown, Professor of Netherlandish Art, University of Oxford "[This book] contains a wealth of fresh and lucidly argued insights, not only into Rembrandt's art, thinking and practice: notably, a significant place is reserved for such artists as Jan Lievens, Ferdinand Bol, Gerrit Dou, Johannes van Vliet and, unexpectedly, Frans Hals. In these thoughtful reflections on the artist and his milieu, the reader will find many generally accepted notions critically revised." - Eric Jan Sluijter, emeritus professor of Art History at the University of Amsterdam.